Confirmation that somatic mutations of beta‐2 microglobulin correlate with a lack of recurrence in a subset of stage II mismatch repair deficient colorectal cancers from the QUASAR trial. Issue 2 (5th July 2019) - Barrow, Paul; Richman, Susan D; Wallace, Andrew J; Handley, Kelly; Hutchins, Gordon G A; Kerr, David; Magill, Laura; Evans, D Gareth; Gray, Richard; Quirke, Phil; Hill, James
Abstract : Aims: Beta2‐microglobulin (B2M) forms part of the HLA class I complex and plays a role in metastatic biology. B2M mutations occur frequently in mismatch repair‐deficient colorectal cancer (dMMR CRC), with limited data suggesting they may protect against recurrence. Our experimental study tested this hypothesis by investigating B2M mutation status and B2M protein expression and recurrence in patients in the stage II QUASAR clinical trial. Methods and results: Sanger sequencing was performed for the three coding exons of B2M on 121 dMMR and a subsample of 108 pMMR tumours; 52 with recurrence and 56 without. B2M protein expression was assessed by immunohistochemistry. Mutation status and protein expression were correlated with recurrence and compared to proficient mismatch repair (pMMR) CRCs. Deleterious B2M mutations were detected in 39 of 121 (32%) dMMR tumours. Five contained missense B2M ‐variants of unknown significance, so were excluded from further analyses. With median follow‐up of 7.4 years, none of the 39 B2M ‐mutant tumours recurred, compared with 14 of 77 (18%) B2M‐ wild‐type tumours ( P = 0.005); six at local and eight at distant sites. Sensitivity and specificity of IHC in detecting B2M mutations was 87 and 71%, respectively. Significantly ( P < 0.0001) fewer (three of 104, 2.9%) of the 108 pMMR CRCs demonstrated deleterious B2M mutations. One pMMR tumour, containing a frameshift mutation, later recurred. Conclusion: B2M mutations were detected in nearly one‐third of dMMR cancers, none of which recurred. B2M mutation status has potential clinical utility as a prognostic biomarker in stage II dMMR CRC. The mechanism of protection against recurrence and whether this protection extends to stage III disease remains unclear.